Breakaway oxidation behaviour of ferritic stainless steels at 1150 °C in humid air. (July 2016) - Cheng, Xiawei; Jiang, Zhengyi; Monaghan, Brian J.; Wei, Dongbin; Longbottom, Raymond J.; Zhao, Jingwei; Peng, Jianguo; Luo, Ming; Ma, Li; Luo, Shuzheng; Jiang, Laizhu
Highlights: The breakaway oxidation behaviour of stainless steels was studied at 1150 °C in humid air. Two ferritic stainless steels with similar Cr content displayed significantly different breakaway oxidation behaviour. The microstructure and composition of oxide scale affected Cr vaporisation greatly. Grain size had little effect on the Cr depletion at 1150 °C. Abstract: The breakaway oxidation behaviour of ferritic stainless steels 430, 443 and 445 has been investigated at 1150 °C in humid air. The oxidation kinetics exhibited significant differences among the three ferritic stainless steels. A uniform and steady growing oxide scale was developed on the 430 steel with an even steel/oxide interface. Local breakdown of the initially protective oxide scale occurred and oxide nodules were developed on the 443 and 445 stainless steels, resulting in irregular and rough steel/oxide interfaces. The breakaway oxidation behaviour was significantly influenced by the microstructure and the composition of the oxide scale. The Mn-Cr spinel oxide formed on top of the Cr2 O3 scale in Mo alloying 445 steel can greatly minimise the Cr depletion.